EOCENE, OLIGOCENE AND MIOCENE NATICID GASTROPODS OF NORTHERN ITALY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
The present paper covers 77 species and six subspecies of naticid gastropods occurring in the Eocene, Oligocene and Miocene units of Northern Italy; all are described and commented on in the systematic account. Forty-two taxa are identified as formerly described ones; of these, 16 are associated with a generic name different from the previous one, and four are ranked at a different taxonomic level. Twenty-four taxa are proposed as new and the rest likely represent undescribed species, but more, better preserved material is required in order to establish their identity and to name them. Of the 83 taxa considered, 17 are assigned to the genus Cochlis Röding, 1798, one belongs in Cryptonatica Dall, 1892, another belongs in Tanea Marwick, 1931, 11 are members of the genus Tectonatica Sacco, 1890, three are included in Ampullonatica Sacco, 1890, one belongs in Eunaticina Fischer, 1885, 20 are assigned to Euspira Agassiz in J. Sowerby, 1837, three belong in Neverita Risso, 1826, five belong in Payraudeautia Bucquoy, Dautzenberg & Dollfus,1883, two agree with the characters of Pliconacca Cossmann & Martin in Martin, 1914, four are members of Polinices Montfort, 1810, two belong in Sigatica Meyer & Aldrich, 1886, four belong in Sigaretotrerma Sacco, 1890, and nine have the characters of the genus Sinum Röding, 1798. All genera are discussed in terms of type species designation, distinctive characters and subfamilial affiliation (when different from the current one).  The character analysis has shown that the measurable elements of the protoconch along with its microsculpture (if any) are diagnostic in many species of all subfamilies. The features of the outer surface of the calcareous operculum proved to be diagnostic in the Pliocene and Recent naticine species. In the present case, the operculum of only four Cochlis species is known, readily differentiating them from one another. The umbilical characters, i.e. umbilicus width and presence/absence and strength of inner spiral structures, proved to be of variable utility in identifying species. The inner umbilical characters are never species-diagnostic in the case of the naticine taxa, particularly those of Cochlis. The inner structures, primarily presence/absence, number and strength of cordlets or threads on the umbilical bottom, are more effective in distinguishing poliniceine taxa. The umbilical callus can be used diagnostically for a limited number of naticine and poliniceine taxa. The exterior sculpture of the teleoconch (absent in the naticine and in most poliniceine taxa) is well developed in all the sinine species. In the case of Sigaretotrema and Sinum, the sculptural characters proved to be relevant in species recognition. The color pattern is diagnostic in most of the taxa in which this character is preserved. The shell morphology and the apertural characters are relevant only in a few cases. In the absence of diagnostic elements, a combination of all characters can help in recognizing species.